2014
DOI: 10.1109/tevc.2013.2281531
|View full text |Cite
|
Sign up to set email alerts
|

Ant Colony Optimization for Mixed-Variable Optimization Problems

Abstract: In this paper, we show how ant colony optimization (ACO) may be used for tackling mixed-variable optimization problems. We show how a version of ACO extended to continuous domains (ACO R ) may be further used for mixed-variable problems. We present different approaches to handling mixed-variable optimization problems and explain their possible uses. We propose a new mixed-variable benchmark problem. Finally, we compare the results obtained to those reported in the literature for various real-world mixed-variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(102 citation statements)
references
References 63 publications
0
102
0
Order By: Relevance
“…The problems of simultaneous handling of quantitative and ordinal data have got least attention of the researchers. Only Hsieh and Tong (2001), Wu (2008) and Liao et al (2014) have attempted to optimize simultaneously the quantitative and ordinal responses. Hsieh and Tong (2001) applied artificial neural networks for simultaneous optimization of quantitative and ordinal responses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems of simultaneous handling of quantitative and ordinal data have got least attention of the researchers. Only Hsieh and Tong (2001), Wu (2008) and Liao et al (2014) have attempted to optimize simultaneously the quantitative and ordinal responses. Hsieh and Tong (2001) applied artificial neural networks for simultaneous optimization of quantitative and ordinal responses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, availability of an appropriate methodology which is capable of optimizing all the quantitative and ordinal variables simultaneously can truly satisfy the practical need of the industries. It is observed that only Hsieh and Tong (2001), Wu (2008) and Liao et al (2014) have attempted to optimize quantitative and ordinal response variables simultaneously under Taguchi's framework of robust design approach. Hsieh and Tong (2001) applied artificial neural networks for simultaneous optimization of quantitative and ordinal responses.…”
Section: Introductionmentioning
confidence: 99%
“…ACO MV [3] is applied to mixed variables optimization problems with r real-valued variables, c categorical-valued variables and o ordinal-valued variables. The ACO MV uses a solution archive (SA) as a form of pheromone model, instead of a pheromone matrix.…”
Section: Aco MVmentioning
confidence: 99%
“…In this paper we propose a new approach to extract IF-THEN of classification rules, based on the ACO for mixedvariable optimization (ACO MV ) [3]. Our approach handles the mixed attributes directly: attributes are categorized as continuous, ordinal and categorical attributes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many comparisons made between the performance of BABC and other optimization algorithms such as Genetic Algorithm (GA) [40], Genetic Programming (GP) [40][41], Evolutionary Strategy (ES) [42], Evolutionary Programming (EP) [40,43], PSO and also Ant Colony Optimization (ACO) [44][45]. In those comparisons, ABC has been proven to outperform the other algorithms in solving multimodal and multidimensional optimization problems with using less control parameters [35][36][37] and the ability to escape from local minima [38].…”
Section: Introductionmentioning
confidence: 99%